(untitled) (Research, Society and Development, 2021)
Since the beginnings of the science of caring for human beings, religious practices and spirituality face a rigorous look from scientists and researchers. Nursing care must provide care and safety measures to the individual under a biopsychosocial unit model, in all physical, social, economic, spiritual and cultural aspects. In this way, this article aimed to analyze the scientific productions about the benefits of religious practices in the provision of nursing care, and specifically describe the importance of religious practices in health status, highlight the main limitations and challenges in nursing care with cultural-religious healing practices and relating nursing behavior to cultural/religious treatment and/or therapy. This is an integrative literature review, in which the question was formulated: "What are the benefits of the association between religious practices and nursing care in the provision of care?". Using descriptors and keywords, the Bireme, CINAHL and PubMed databases were consulted. We used the available studies in full, published in the years 2015 to 2020, in English, Portuguese and Spanish. The articles showed that religiosity and spirituality are fundamental dimensions in the healing, rehabilitation and overcoming processes, and should be implemented in the science of care by health professionals. It was concluded that it is the duty of nursing and other areas of health to serve the individual with humanized care, respecting their spiritual-religious needs in treatment and/or therapy.